Usefulness of Artificial Membrane, Strat-M®, in the Assessment of Drug Permeation from Complex Vehicles in Finite Dose Conditions - Florencio Jr Arce; Narumi Asano; Gerard Lee See; Shoko Itakura; Hiroaki Todo; Kenji Sugibayashi (MDPI AG, 2020)
The ban on the use of animals in testing cosmetic products has led to the development of animal-free in vitro methods. Strat-M® is an artificial membrane engineered to mimic human skin and is recommended as a replacement for skin. However, its usefulness in the assessment of the permeation of cosmetics in in-use conditions remains unverified. No data have been published on its comparative performance with the membrane of choice, porcine skin. The comparative permeability characteristics of Strat-M® and porcine skin were investigated using Franz diffusion cells. Caffeine (CF) and rhododendrol (RD) in complex vehicles with varying concentrations of polyols were applied as finite and infinite doses. Good rank orders of permeation from finite dose experiments were observed for RD. High correlations were observed in RD permeation between Strat-M® and porcine skin under finite and infinite dose conditions, whereas only finite dose conditions for CF were associated with good correlations. Permeation from formulations with high polyol content and residual formulations was enhanced due to the disruption of the integrity of the Strat-M® barrier. The usefulness of Strat-M® in the assessment of dermal permeation may be limited to finite dose conditions and not applicable to infinite dose conditions or formulations applied in layers.